Water Quality and Its Appropriate Use for Society in Hargowilis, West Progo - Sri Ning Peni; T. Listyani R.A. (Retii, 2018)
Hydrochemical survey has been done in Hargowilis Village, West Progo, around Sermo Paunch. This area is located at West Progo Hills physiography which is water ever be important problem because of its lack of water. This research wants to know about water quality in research area and its appropriate use for local people. The survey has been carried out for collecting some data of quality water by geological equipment such as GPS, hammer, compass, loupe, sample bottle and hydrochemical tools like thermometer, pH-meter, as well as TDS- meter. Four samples of water have been taken from stream, lake, spring and dug well and have been tested in chemical laboratory. Result of research shows that water in Hargowilis has pH of 6.1 - 8.4 and TDS of 108-1659 ppm. This water is suitable for clean water, drink water and irrigation (in form of S1C1 and S1C4 types). Although there is dug well found with bad quality water because of its water with very high salinity hazard.